Students’ Beliefs And Strategies In Learning Pronunciation : A Narrative Research - Hasanuddin Fatsah; Muzdalifah Mahmud; Indy Rahmawani Malle (Journal of Language Education (JoLE), 2026)
This study aims to explore students’ beliefs and strategies in learning English pronunciation. Employing a qualitative approach with narrative inquiry as the research design, this study focuses on understanding learners’ experiences through their personal stories and reflections. The participants were students of the English Language Education Study Programme who had experience in learning English pronunciation. Data were collected through in-depth interviews to capture participants’ beliefs, learning experiences, and strategies related to pronunciation learning. The data were analyzed thematically by identifying recurring patterns and key themes across the narratives. The findings reveal that students hold varied beliefs about English pronunciation learning, particularly regarding the importance of accuracy, exposure, and practice. In addition, students employed diverse strategies such as self-practice, listening to authentic materials, repetition, and seeking feedback to improve their pronunciation skills. This study contributes to a deeper understanding of learners’ perspectives on pronunciation learning and provides practical implications for English pronunciation teaching in higher education contexts.